TOKSISITAS (LC50 dan LT50) JAMUR ENTOMOPATOGEN Beauveria bassiana (Bals.) Vuill. TERHADAP HAMA ULAT GRAYAK (Spodoptera litura F.) - Jauharlina Jauharlina; Hendrival Hendrival (Fakultas Pertanian, Universitas Syiah Kuala, 2003)
Toxicity of enthomopathogenic fungi Beauveria bassiana to armyworm (Spodoptera litura) has been investigated in Pest Laboratory of Faculty of Agriculture, Syiah Kuala University, Darussalam, Banda Aceh. This research was aimed at determining lethal concentration (LC50) and lethal time (LT50) of B. bassiana suspensions against third instar larvae of armyworm. The fungi concentration used was in the range 0-6 % (w/v) or equal to 9,33 x 106 – 45,83 x 106 conidia/ml. The fungi suspension was applied to the larvae by dissolving the larvae into the suspension for 10 seconds. The number of the larvae died and the time required to kill the larvae were recorded everyday starting one day after application (DAA) until pupation. The relation between each observation to the fungi concentration was analyzed using probit analysis. The result showed that B. bassiana suspension caused the death of the larvae beginning 4 DAA with maximum eath on 10 DAA. The death of the larvae caused by the growth and the development of the fungi inside the larvae. The LC50 of the fungi suspension against the larvae was 3,57 % while the LT50 at 4, 5, and 6 % fungi concentration were 9,88; 8,13; and 6,8 days respectively.